Collaborative learning interventions for elementary students’ mathematical creative reasoning: A meta-analysis - Cholifah, Tety Nur; Soetjipto, Budi Eko; Setyosari, Punaji; Untari, Sri (Journal of Interdisciplinary Studies in Education, 2026)
This meta-analysis synthesizes experimental and quasi-experimental evaluations of collaborative learning interventions for elementary students’ mathematical creative reasoning (CMR). After a verification audit, 30 studies (N = 3,108) from 11 countries (1997–2024) met the inclusion criteria. A random-effects model yielded a large effect (Hedges’ g = 1.58, 95% CI [1.46, 1.70], p < .001) with moderate heterogeneity (I² = 42.1%), interpreted cautiously given that 50% of studies were Indonesian; the non-Indonesian subsample yielded g = 1.49. Open-ended/multiple solution tasks and problem-based learning produced the largest effects; instructional time was not a significant moderator. The findings imply that higher-education teacher preparation should embed evidence-based collaborative pedagogies to ensure curriculum continuity in tertiary mathematics education.